Assessing primate’s pelage colour using RGB method in Malayan Pale-thighed Surili (Presbytis siamensis siamensis) - Siti Nur Aliah, Mohd Isa; Mohd Ridwan, Abd Rahman; Md Zain, Badrul Munir (Department of Environmental Sciences, Arak University, 2023)
The Red, Green and Blue (RGB) colour model has been used to investigate relationships between primates' physiological and colour data. This study uses the RGB method to determine various pelage hues in white-thighed surili at different latitudes in Peninsular Malaysia. Universiti Kebangsaan Malaysia (UKM) represents the lowland while Genting Highlands and Fraser’s Hill represent the highland area. Results indicated that no significant values were found based on the sample t-test on every section of the samples except on the nose (Green). Our findings can be utilised further for systematic and population genetic studies of Presbytis siamensis siamensis in Peninsular Malaysia.